SURVEI AKTIVITAS FISIK TERHADAP SIKLUS MENSTRUASI PADA MAHASISWI FIKKM UNDIKMA TAHUN 2021 - Intan Kusuma Wardani (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2022)
Almost every woman has experienced menstrual cycle irregularities. Strenuous physical activity is known as one of the factors that women experience menstrual cycle disorders. This study aims to obtain survey data on physical activity on the menstrual cycle of FIKKM UNDIKMA students in 2021. The design of this research is descriptive quantitative with a survey method. The population in this study were 132 students of FIKKM UNDIKMA class 2021 with a sample size of 40 respondents. In this study using purposive sampling. Data collection techniques using questionnaires and analysis using Chi-Square Test. The results of the study of respondents who experienced irregular menstruation on light activities were 4 people (10%), moderate physical activity were 2 people (5%), and heavy physical activity was 11 people (27.5%). Respondents who experienced regular menstruation on physical activity were 10 people (25%), moderate physical activity were 12 people (30%), and heavy physical activity was 1 person (2.5%). Analysis of the relationship obtained x2 count (7.3) > x2 table (5.991) which means H0 is rejected and H1 is accepted which means there is a relationship between physical activity and menstrual cycle disorders. It is expected that respondents who have light physical activity can increase physical activity with sufficient exercise, while those who have heavy physical activity are expected to reduce their activity a little so that the menstrual cycle is not disturbed